Resonance-enhanced multiple ionization of krypton at an x-ray free-electron laser - Rudek, Benedikt; Rolles, Daniel; Son, Sang-Kil; Foucar, Lutz; Erk, Benjamin; Epp, Sascha; Boll, Rebecca; Anielski, Denis; Bostedt, Christoph; Schorb, Sebastian; Coffee, Ryan; Bozek, John; et al. (My University, 2013)
The sequential inner-shell multiple ionization of krypton was investigated at the Linac Coherent Light Source using ion time-of-flight spectroscopy at photon energies above (2 keV) and below (1.5 keV) the L edge with two x-ray pulse lengths (5 and 80 fs, nominally) and various pulse energies. At 2.5 mJ pulse energy, charge states up to Kr17+ were recorded for M-shell ionization and charge states up to Kr21+ for L-shell ionization. Comparing the experimental charge state distribution to Monte Carlo rate-equation calculations, we find a strong enhancement of higher charge states at 2 keV photon energy as compared to the theoretical predictions. This enhancement is explained with a resonant ionization pathway where multiple excitations into outer valence and Rydberg orbitals are followed by autoionization. These resonant pathways play an important role for the photoionization of ions with charge higher than Kr12+, for which direct one-photon L-shell photoionization is energetically impossible at 2 keV photon energy. Only a small pulse-length dependence of the charge state yield is observed at an x-ray pulse energy of 0.4 mJ.